The point of epiphyseal penetration affects rotational stability of screw fixation in slipped capital femoral epiphysis: A biomechanical study. Issue 12 (22nd May 2020) - Morris, William Z.; Riccio, Anthony I.; Podeszwa, David A.; Pierce, William A.; Standefer, Karen D.; Kiapour, Ata; Liu, Raymond W.; Novais, Eduardo N.
Abstract: The epiphyseal tubercle, a posterosuperior projection of the epiphysis into the metaphysis, serves as the axis of rotation in slipped capital femoral epiphysis (SCFE) and a source of physeal stability. We hypothesized that in a biomechanical model of single screw fixation of stable SCFE, a screw passing through the epiphyseal tubercle (the axis of rotation) would confer less rotational stability than a centrally placed screw. Three femurs were selected from a sample population of 8‐ to 15‐year‐old healthy hips to represent three stages of maturation: a "young" femur with a prominent epiphyseal tubercle and decreased epiphyseal cupping around the metaphysis, a "median" femur with a subsiding tubercle, and a "mature" femur with a subsided epiphyseal tubercle and increased peripheral epiphyseal cupping. Specimens were three‐dimensional printed with one of two screw trajectories: passing centrally in the epiphysis or directly through the epiphyseal tubercle. Resistance to rotational displacement was measured through stiffness and maximum torque over 30° degrees of displacement. In the "young" model, epiphyseal tubercle screw position conferred less rotational stiffness and required less maximum torque during rotational displacement when compared to a centrally placed screw ( P  < .001). In the "median" and "mature" models where the tubercle has subsided and is replaced by peripheral epiphyseal cupping, screw position through the tubercle was associated with equal or greater rotational stiffness and maximum torque during displacement as a centrally placed screw.